Progress Toward Regional Measles Elimination — Worldwide, 2000–2021 - Minta, Anna A.; Ferrari, Matt; Antoni, Sebastien; Portnoy, Allison; Sbarra, Alyssa; Lambert, Brian; Hauryski, Sarah; Hatcher, Cynthia; Nedelec, Yoann; Datta, Deblina; Ho, Lee Lee; Steulet, Claudia; et al. (MMWR. Morbidity and mortality weekly report, 2022)
All six World Health Organization (WHO) regions have committed to eliminating measles.* The Immunization Agenda 2021-2030 (IA2030) aims to achieve the regional targets as a core indicator of impact and positions measles as the tracer of a health system's ability to deliver essential childhood vaccines. IA2030 highlights the importance of ensuring rigorous measles surveillance systems to document immunity gaps and achieve 95% coverage with 2 timely doses of measles-containing vaccine (MCV) among children. This report describes progress toward measles elimination during 2000-2021 and updates a previous report (1). During 2000-2021, estimated global coverage with a first MCV dose (MCV1) increased from 72% to a peak of 86% in 2019, but decreased during the COVID-19 pandemic to 83% in 2020 and to 81% in 2021, the lowest MCV1 coverage recorded since 2008. All countries conducted measles surveillance, but only 47 (35%) of 135 countries reporting discarded cases achieved the sensitivity indicator target of two or more discarded cases per 100,000 population in 2021, indicating surveillance system underperformance in certain countries. Annual reported measles incidence decreased 88% during 2000-2016, from 145 to 18 cases per 1 million population, then rebounded to 120 in 2019 during a global resurgence (2), before declining to 21 in 2020 and to 17 in 2021. Large and disruptive outbreaks were reported in 22 countries. During 2000-2021, the annual number of estimated measles deaths decreased 83%, from 761,000 to 128,000; an estimated 56 million measles deaths were averted by vaccination. To regain progress and achieve regional measles elimination targets during and after the COVID-19 pandemic, accelerating targeted efforts is necessary to reach all children with 2 MCV doses while implementing robust surveillance and identifying and closing immunity gaps to prevent cases and outbreaks.